Geographic information system query optimisation algorithm based on redundant data deletion and filtering technology. (2018) - Lu, Chunyang; Wen, Feng
In order to reduce the interference of redundant information during geographic information system query and improve the accuracy of information query, a geographic information system query optimisation algorithm based on redundant data deletion and filtering technology is proposed. In this method, a distributed data query structure model of geographic information system is constructed; adaptive group matching of query intervals is conducted through the segment fusion method, and then key information points after group matching are located through the association rule feature information fusion method. Finally, the high-order cumulant feature extraction method is adopted to achieve accurate information query of geographic information system. Simulation results show that in geographic information system query under redundant data infection, this method can provide accuracy 8.75% higher than that provided by the FCM method and 12.98% higher than that provided by the support vector machine algorithm, which indicates that this method can provide strong anti-interference ability of query and cost less overhead.